The Political and Material Landscape of European Energy Distribution: Tracking the Oil Road. (September 2014) - Marriott, James; Minio-Paluello, Mika
A close analysis of contemporary and historical extraction of Caspian oil and its transportation, via pipeline and tanker, to central Europe, frames an investigation into interrelationships between the organization and conditioning of European societies and their fuel mobility systems. For the fuel used for contemporary mobility systems relies on the mobility systems of fuel. The article examines the governmental and capital structures that have driven oil consumption growth since the 1870s, enabled the powering of geopolitics and determined the spatiality of carbonized sociotechnical systems. It unpacks the current forces that resist any shift away from this petroculture, any 'powering down' of society.